2001
DOI: 10.1128/jb.183.24.7371-7380.2001
|View full text |Cite
|
Sign up to set email alerts
|

RNA Expression Analysis Using an Antisense Bacillus subtilis Genome Array

Abstract: We have developed an antisense oligonucleotide microarray for the study of gene expression and regulation in Bacillus subtilis by using Affymetrix technology. Quality control tests of the B. subtilis GeneChip were performed to ascertain the quality of the array. These tests included optimization of the labeling and hybridization conditions, determination of the linear dynamic range of gene expression levels, and assessment of differential gene expression patterns of known vitamin biosynthetic genes. In minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 41 publications
7
79
0
2
Order By: Relevance
“…However, two candidates for this role, RibC and RibR, which were identified genetically, were later shown to regulate the rib operon indirectly. Both proteins have flavokinase activity and thus decrease the concentration of flavin mononucleotide (FMN), which represses the rib operon [9][10][11]. The repression was shown to involve premature termination of transcription, generating a short transcript corresponding to the 5 0 -untranslated leader of the operon mRNA, and to be abolished by mutations in this region [11].…”
Section: Regulation By Riboswitchesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two candidates for this role, RibC and RibR, which were identified genetically, were later shown to regulate the rib operon indirectly. Both proteins have flavokinase activity and thus decrease the concentration of flavin mononucleotide (FMN), which represses the rib operon [9][10][11]. The repression was shown to involve premature termination of transcription, generating a short transcript corresponding to the 5 0 -untranslated leader of the operon mRNA, and to be abolished by mutations in this region [11].…”
Section: Regulation By Riboswitchesmentioning
confidence: 99%
“…This is not an absolutely universal rule because it does not take into account cases of dual regulation (e.g. the ypaA genes from the Bacillus/Clostridium group, which are regulated both on the transcriptional level [35] and on the translational [14] level). This correlation can also be obscured by horizontal transfer, when a gene or an operon together with the regulating riboswitch is transferred between taxa.…”
Section: Common Features Of Riboswitchesmentioning
confidence: 99%
See 1 more Smart Citation
“…4B,C). One of the bioY paralogs from B. subtilis, yhfU, belongs to the yhfUST operon, and transcription of this operon is repressed by BirA (Lee et al 2001). In addition, yhfU and yhfS-yhfT are clustered in the genomes of B. cereus, Lactococcus lactis, Clostridium difficile, and S. meliloti; whereas Streptococcus pyogenes, Streptococcus equi, and Staphylococcus aureus have separate BirAregulated yhfST and yhfU operons.…”
Section: Aquifex Aeolicusmentioning
confidence: 99%
“…In our previous studies, we found that some intergenic sequences in M. tuberculosis genome exhibited expression signals, as detected by the Affymetrix GeneChip (Fu 2006;Fu and FuLiu 2007;. The same observation has been made for other bacteria, such as Bacillus subtilis (Lee, Zhang et al 2001), and also holds true in the eukaryotic system (Zheng, Zhang et al 2005). At present, it is not clear whether or how intergenic expression represents gene activity.…”
Section: Introductionmentioning
confidence: 73%